3D modelling of long-term sulfide corrosion of copper canisters in a spent nuclear fuel repository. (November 2022) - Ma, Jin; Pekala, Marek; Alt-Epping, Peter; Pastina, Barbara; Maanoja, Susanna; Wersin, Paul
Abstract: Copper canisters are a central component in the safety of the Finnish spent fuel repository concept (KBS-3), where the main corrodent potentially affecting the canister integrity is sulfide. In this study, a 3D numerical model is developed to assess the evolution of sulfide fluxes and the spatially resolved canister corrosion depths for the Finnish spent nuclear fuel repository concept. The backfilled tunnel and the disposal hole are implemented using repository geometries, with sulfide being produced at their interface with the rock (excavation damaged zone) by sulfate reducing bacteria (SRB). Recent experimental findings regarding the microbial sulfate reduction process as well as the scavenging of sulfide via iron (oxy)hydroxides are incorporated in the reactive transport model. Long-term simulations are performed, predicting a heterogeneous corrosion of the canister with a max. corrosion depth of 1.3 mm at the bottom corner after one million years. The evolution of sulfide fluxes shows two main phases, depending on the source of sulfate: first sulfate is supplied by the dissolution of gypsum from the bentonite barriers, followed by a steady, low-level supply from the groundwater. Sensitivity cases demonstrate that both the organic carbon and Fe(III) oxide contents in the bentonite are critical to the corrosion evolution, by being the main electron donor for SRB activities and the major sulfide scavenger in the bentonite, respectively. The backfilled tunnel contributes little to the flux of corrosive sulfide to the canister due to the attenuation by Fe(III)-oxides/hydroxides but induces a notable flux of sulfate into the disposal hole. Graphical abstract: Image 1 Highlights: A 3D reactive transport model is developed based on KBS-3 SNF repository. Sulfide system display two major phases during a 1 Mio year simulation. Heterogeneous corrosion of the copper canister is predicted. Organic carbon and Fe(III) oxide contents are critical to sulfide corrosion. Backfill induces little sulfide but notable sulfate fluxes into disposal hole.